Digital Era: Review Of The Phenomenon Of Islamic Economic & Business Transformation - Hidayat, Agus (Prodi Ekonomi Syariah, Fakultas Syariah dan Hukum, Universitas PTIQ Jakarta, 2024)
This research examines the transformation of the business economy in the digital era from an Islamic economics perspective. A qualitative approach with content analysis is used to analyze how Islamic economic principles are applied in digital business. The findings reveal growing interest in this area and highlight the importance of integrating Islamic economic principles with digital technologies. The research concludes that Islamic economics can be a valuable guide for businesses facing the challenges of the digital era and emphasizes the need for ethical considerations in adopting new technologies.